New taxa and new records of Winnertziinae and Porricondylinae (Diptera: Cecidomyiidae) from Germany - Jaschhof, Mathias (European Journal of Taxonomy, 2024)
Winnertziinae and Porricondylinae are two subfamilies of mycophagous Cecidomyiidae (gall midges). An earlier census in 2021 found the German fauna of both groups to comprise 53 species and 28 genera – only a small proportion of the nearly 400 species and 75 genera known from all of Europe. A 24-month inventory in 2021‒2023, whose most significant taxonomic and faunistic outcomes are presented here, yielded evidence of an additional 142 species and 24 genera present in Germany, more precisely 41 species and three genera of Winnertziinae, and 101 species and 21 genera of Porricondylinae. Included in these numbers are 30 new species (six Winnertziinae, 24 Porricondylinae) and one new genus (of Porricondylinae) described and named here. The number of potentially new species discovered during the project is considerably larger (85+), but the too poor condition of the specimens and various other circumstances do not permit their taxonomic description at this stage. New taxa named in the present paper are Johnsonomyia szadziewskii sp. nov., Rhipidoxylomyia bilobata sp. nov., Winnertzia haushoferorum sp. nov., Winnertzia incrassata sp. nov., Winnertzia macrodens sp. nov., Winnertzia subdentata sp. nov., all Winnertziinae, Asynapta doczkali sp. nov., Asynapta falcata sp. nov., Bryocrypta longissima sp. nov., Camptomyia serrata sp. nov., Cassidoides rainensis sp. nov., Cassidoides riparius sp. nov., Claspettomyia gracilostylus sp. nov., Claspettomyia parvidentata sp. nov., Divellepidosis bavarica sp. nov., Lamellepidosis luderbuschensis sp. nov., Neurepidosis hartschimmelhofensis sp. nov., Neurepidosis simplex sp. nov., Parepidosis lobata sp. nov., Porricondyla acutistylata sp. nov., Porricondyla insolita sp. nov., Porricondyla oblonga sp. nov., Porricondyla ornata sp. nov., Porricondyla pilosoides sp. nov., Porricondyla plana sp. nov., Porricondyla pumila sp. nov., Schistoneurus paraimpressus sp. nov., Schistoneurus subimpressus sp. nov., Spungisomyia germanica sp. nov., Wohllebenia gen. nov., and Wohllebenia hybrida gen. et sp. nov., all Porricondylinae. Taxonomic descriptions are based on both the morphology of males and, if available, CO1 (DNA barcode) sequences, using specimens collected by Malaise traps in Bavaria and Baden-Württemberg, the two southernmost federal states of Germany. Released here are 150 BINs new to BOLD as well as 145 species names for previously unidentified BINs in BOLD. Redescriptions of male morphology are provided for Camptomyia heterobia Mamaev, 1961, Claspettomyia carpatica Mamaev, 1998, Dicerura scirpicola Kieffer, 1898, and Winnertzia betulicola Mamaev, 1963. The state of knowledge of Germany’s fauna of mycophagous gall midges is discussed.